Pengaruh Perilaku WPS Dalam Pencarian Pengobatan PMS, Lingkungan Dan Status Kesehatan Terhadap Kualitas Hidup WPS Di Kelurahan Dadap Tangerang Tahun 2011 - Siti Rafika Putri (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2016)
Sexually transmitted diseases are a public health problem in the world, including in Indonesia. WPS issuspected as the spread of sexually transmitted diseases caused by free sex behavior. PMS is a lot ofpeople who do not perform the treatment at health facilities resulting in lower quality of life andhealth status of patients. Knowing the purpose of this study is WPS influence behavior in the searchfor treatment of PMS, environment, health status on quality of life in the Village Dadap TangerangWPS in 2011. This study uses cross-sectional design, primary data. Sample of 108 people. WPSvariables studied in the search for treatment of behavioral, environmental, health status, quality oflife, enabling factors, predispocing factors, reinforcing factors. Data processing using SmartPLS(partical least squares). The results of the analysis is the quality of life is directly affected by the WPSand the environmental health status, and indirectly influenced by the reinforcing factor in the Villageof Tangerang Dadap in 2011. Therefore, if there is further research with a similar theme, it isnecessary to develop the variables, indicators, and new theories gained.